2019
DOI: 10.9734/irjpac/2019/v19i430120
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pesticide Residues in Fresh Vegetables from Three Major Markets in Lagos Using QuEChERS Method and GC-MS

Abstract: The study evaluates pesticide residues in fresh vegetables from three major markets in Lagos and verified compliance of these fresh vegetables with the maximum residue levels (MRLs) as specified by Codex Alimentarius Commission. The residues were extracted by means of multi residue method based on the Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) method, Gas Chromatography - Mass Spectrometry (GC-MS) was used to determine two organophosphates (dichlorvos and chlorpyrifos), two organochlorines (endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Limit (MRL) as defined as the highest levels of pesticide residues legally tolerated in foodstuffs [33], which is permissible as the highest limit authorized by Codex Alimentarius commission (2019a) [11]. It was observed that all pesticide residues found in mango and guava fruits before rinsing at 80 C˚/60sec and after pasteurization processes mango and guava pulp did not exceed the maximum residue limit (MRL) as illustrated in the same Table (1), as authorized by Codex Alimentarius commission (2019a) [11].…”
Section: Results In Table 1 Were Compared With the Maximum Residuementioning
confidence: 99%
“…Limit (MRL) as defined as the highest levels of pesticide residues legally tolerated in foodstuffs [33], which is permissible as the highest limit authorized by Codex Alimentarius commission (2019a) [11]. It was observed that all pesticide residues found in mango and guava fruits before rinsing at 80 C˚/60sec and after pasteurization processes mango and guava pulp did not exceed the maximum residue limit (MRL) as illustrated in the same Table (1), as authorized by Codex Alimentarius commission (2019a) [11].…”
Section: Results In Table 1 Were Compared With the Maximum Residuementioning
confidence: 99%
“…However, the pesticide concentrations mostly do not reach the legislatively set-up MRLs [ 192 ]. MRLs are the highest concentrations of pesticides allowed to be present in foodstuffs [ 193 ]. Nonetheless, simultaneous human exposure to more than one pesticide in food is potent to induce synergistic effects, even though the specific pesticide concentrations alone are safe, as reviewed in Kortenkamp [ 194 ].…”
Section: Environment As a Source Of Bread Chemical Contaminantsmentioning
confidence: 99%